Effect of aerobic exercise on frequency of vaginal birth – A meta-analysis - Bubnjević, Ksenija; Macura, Marija; Jakovljević, Aleksandra; Borisavljević, Aleksandar; Đoković, Novica (Vojnosanitetski pregled, 2022)
Background/Aim. Pregnancy is a state where different morphological and physiological changes occur in a pregnant woman's body. There are many factors that have an effect on maintaining a healthy pregnancy. Physical activity is one of the possible factors that can have an impact on the quality of life during pregnancy. Healthy pregnant women, without medical or obstetric complications, are advised to exercise in a moderate and proper manner. The aim of this meta-analysis was to evaluate the impact of continuous aerobic exercise on the frequency of vaginal birth in healthy pregnant women with normal body mass index (BMI) values. Methods. This meta-analysis was based on a systematic review and selection of randomized clinical trials. The affect of physical exercise was assessed using the "RStudio" programming language and environment. Heterogeneity of studies was assessed by Q statistics. Possible publication bias of studies was identified. The primary outcome analysis was related to the frequency of vaginal birth, while the secondary outcome analysis was related to BMI in the first measurement and total weight gain after the second measurement. The suitability of 10 individual studies is shown by graphical and statistical analysis of the extracted data. Results. Physically active pregnant women who exercised with light to moderate intensity 3 times a week (35–60 minutes), had a more frequent vaginal birth than sedentary pregnant women (67.4% vs. 60.5; relative risk (RR) 1.11, 95% confidence interval (CI), 1.04–1.18). RR was statistically significantly different from unit (p = 0.002). All pregnant women had optimal BMI values in the first measurement before intervention. Also, all pregnant women gained the recommended number of kilograms during pregnancy. Conclusion. Analysis of selected individual studies showed that continuous aerobic physical exercise during the second and third trimesters does not have a negative effect on measured outcome of pregnancy. Physically active pregnant women were more likely to give birth vaginally than sedentary pregnant women.
Keywords: delivery, obstetric; exercise; meta-analysis; pregnancy; pregnancy outcome